Technology and Film Scholarship : Experience, Study, Theory - Gaudreault, Andre; Hidalgo, Santiago (Book collections on Project MUSE., 2018)
This volume brings together a wide range of research on the ways in which technological innovations have established new and changing conditions for the experience, study and theorization of film. Drawn from the IMPACT film conference (The Impact of Technological Innovations on the Historiography and Theory of Cinema) held in Montreal in 2011, the book includes contributions from such leading figures in the field as Tom Gunning, Charles Musser, Jan Olsson and Vinzenz Hediger.